Analysis of Pegadaian Digital Services Based on User Satisfaction Using D&M IS Success Model - Witjaksono, Gunawan; Sentanu, Vilosa Auliya Dewinta (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2024)
This study aims to determine the significance of variables and the success of the Pegadaian Digital Services (PDS) application utilizing the DeLone & McLean Information System (D&M IS) Success Model in the Jabodetabek area. This research method uses a quantitative approach, collecting data through questionnaires to active users of the PDS application in Jabodetabek. The collected data was processed using the SEM-PLS model with the SMARTPLS3 tool. The findings indicate that user satisfaction is significantly impacted by system quality, information quality, as well as service quality. However, net benefits are not strongly influenced by user satisfaction. Nevertheless, net gain is not much impacted by user satisfaction. Furthermore, both system quality and information quality also have a significant and positive effect on net benefit. The overall success rate of the PDS application is 84% which means that the PDS application is very successful, which is analyzed from the user’s perspective and the D&M IS Success Model is effective in measuring application success. This finding is expected to be an evaluation material in improving the quality of PDS applications and for further research can expand the coverage area, explore additional factors, and conduct research with direct interviews with users.